2013
DOI: 10.1021/es403079h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Material Morphology on the Phototoxicity of Nano-TiO2 to Bacteria

Abstract: Nanostructured titania (nano-TiO2) is produced in diverse shapes, but it remains largely unknown how tuning the morphology of nano-TiO2 may alter its toxicity. Herein, we show that material morphology plays a critical role in regulating the phototoxicity of nano-TiO2 to bacteria. Low-dimensional nano-TiO2, including nanotubes, nanorods, and nanosheets, were synthesized hydrothermally, and their effects on the bacterial viability of Escherichia coli and Aeromonas hydrophila were compared to spherical nanostruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 63 publications
3
90
0
Order By: Relevance
“…While ZnO shows strong antibacterial properties under ambient radiation, TiO2 generally responds under UV radiation [169,170]. Methods for completing the photocatalysis of waterborne microorganisms into visible and solar light energy have been obtained by making composites, design of core-shell type nanostructures, nanoparticle doping, surface wettability patterning, offset printing, or increase of crystal defect [170].…”
Section: Water Disinfection and Air Cleansingmentioning
confidence: 99%
“…While ZnO shows strong antibacterial properties under ambient radiation, TiO2 generally responds under UV radiation [169,170]. Methods for completing the photocatalysis of waterborne microorganisms into visible and solar light energy have been obtained by making composites, design of core-shell type nanostructures, nanoparticle doping, surface wettability patterning, offset printing, or increase of crystal defect [170].…”
Section: Water Disinfection and Air Cleansingmentioning
confidence: 99%
“…Previous studies suggested that the antibacterial activities of TiO 2 -based materials were attributed to photocatalytic activity for generating reactive oxygen species (ROS), such as •OH radicals [37] . These ROS may produce oxidative stress and then attack membrane lipids, ultimately leading to membrane or DNA damage.…”
Section: Synergistic Antibacterial Mechanism Of Tio 2 /Ag Compositesmentioning
confidence: 99%
“…The decrease in bacterial abundance was first noted 1 day after addition, but bacterial numbers returned to control levels within 3 weeks. Multiple previous studies have demonstrated the toxicity of nano-TiO 2 to bacteria [11,15,[17][18][19][20] and have confirmed that the toxicity of nano-TiO 2 is due primarily to its production of ROS when illuminated [11], but these studies have been conducted with both the bacteria and nano-TiO 2 particles mixed in suspension. The toxicity of nano-TiO 2 to sediment-associated organisms that was observed in this study under realistic environmental conditions is novel, and it is significant because of the ecological importance of benthic microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Nano-TiO 2 has been shown to be toxic to aquatic organisms, including fish [12][13][14], invertebrates [15][16][17], bacteria [11,15,[17][18][19][20], cyanobacteria [21,22], and algae [22][23][24][25][26]. Most studies demonstrating the toxicity of nano-TiO 2 have been conducted with model organisms under laboratory conditions, although a few have attempted to model more realistic environmental conditions.…”
Section: Introductionmentioning
confidence: 99%